PENGARUH SERTIFIKASI GURU TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI - Nurfitriani, Annisa; Witurachmi, Sri; Ivada, Elvia (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objectives of this research are to investigate: (1) the effect of teacher certification on the learn-ing motivation in Accounting learning, and (2) the effect of teacher certification on the learning achieve-ment in Accounting learning. This research used the descriptive comparative research method by compar-ing two groups of students taught by two certified teachers and two non-certified teachers. The population was all of the students of Accounting Department of State Vocational High Schools of Surakarta. The sam-ples of research are determined by using purposive sampling technique (the students were taking the Ac-counting subject matter taught by two certified teachers and two non-certified teachers). They consisted of 128 students. The students were taking the Accounting subject matter taught by two certified teachers and two non-certified teachers. The data of research were collected through questionnaire of learning motiva-tion with Likertâs scale and test of learning achievement. They were analyzed by using t-test analysis with the computer program of software SPSS Version 20 for Windows at the significance level of 5%.The re-sults of t-test analysis are as follows: (1) the teacher certification has a positive effect on the learning mo-tivation in Accounting subject matter with the probability value = 0.002 (p<0.05); and (2) the teacher cer-tification has a positive effect on the learning achievement in Accounting subject matter with the probabil-ity value = 0.000 (p<0.05).Keywords : Teacher Certification, Learning Motivation, Learning AchievementABSTRAKTujuan penelitian ini adalah untuk mengetahui pengaruh: (1) sertifikasi guru terhadap motivasi belajar siswa pada mata pelajaran akuntansi, (2) sertifikasi guru terhadap prestasi belajar siswa pada mata pelajaran akuntansi.Penelitian ini merupakan jenis penelitian deskriptif komparatif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa jurusan akuntansi di SMK Negeri Surakar-ta. Teknik pengambilan sampel yang digunakan adalah purposive sampling (siswa yang menempuh mata pelajaran dimana terdapat guru tersertifikasi dan non-sertifikasi yang mengajar mata pelajaran tersebut). Jumlah sampel yang digunakan adalah 128 siswa. Teknik pengumpulan data yang digunakan adalah angket dengan skala likert untuk data motivasi belajar dan teknik tes untuk data prestasi belajar. Teknik analisis data yang digunakan adalah uji-t (t-test) dengan bantuan Software SPSS Versi 20 for Windows dengan nilai signifikansi 5%. Hasil dari penelitian ini menunjukkan bahwa: (1) sertifikasi guru ber-pengaruh positif terhadap motivasi belajar siswa pada mata pelajaran akuntansi dengan nilai probabilitas sebesar 0.0002 (p<0.05), dan (2) sertifikasi guru berpengaruh positif terhadap